2010
DOI: 10.1016/j.cellsig.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Serine Threonine Receptor-Associated Protein (STRAP) plays a role in the maintenance of mesenchymal morphology

Abstract: The stromal tissue, made of extracellular matrix and mesenchymal cells, is vital for the functional design of all complex tissues. Fibroblasts are key components of stromal tissue and play a crucial role during organ development, wound repair, angiogenesis and fibrosis. We have previously reported the identification of a novel WD-domain protein, STRAP1 that inhibits transforming growth factor-β (TGF-β) signaling and enhances tumorigenicity via TGF-β-dependent and TGF-β-independent mechanisms. Here, we report, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
14
1
Order By: Relevance
“…Additionally, STRAP physically interacts with PDK1 and positively modulates its downstream targets such as PKB/Akt and Bad in vivo (17). Our recent studies showed that STRAP transcriptionally downregulates E-cadherin and p21 Cip1 expressions (18), and it promotes the mesenchymal phenotype (19). …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, STRAP physically interacts with PDK1 and positively modulates its downstream targets such as PKB/Akt and Bad in vivo (17). Our recent studies showed that STRAP transcriptionally downregulates E-cadherin and p21 Cip1 expressions (18), and it promotes the mesenchymal phenotype (19). …”
Section: Introductionmentioning
confidence: 99%
“…[15][16] We have previously reported STRAP plays a role in maintenance of mesenchymal morphology by downregulating E-cadherin in mRNA levels, 9 which raises a possibility that STRAP might interrupt some transcription factor(s) binding to the promoter resulting in reduced transcription. So we first decided to analyze the mechanism of regulation of E-cadherin by STRAP.…”
Section: Strap Inhibits Sp1-dependent Activation Of E-cadherin Promotermentioning
confidence: 99%
“…13 We have previously reported that STRAP is involved in maintaining mesenchymal morphology by regulating E-cadherin and that it enhances tumorigenicity partly by downregulating CDK inhibitor p21 Cip1 . 9,10,12 but the functional mechanism of regulation of E-cadherin and p21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STRAP lacks kinase activity but has 7 WD domains, which are responsible for protein-protein interactions. There are also reports that STRAP inhibits transforming growth factor (TGF) signaling by interacting with TGF-␤ receptor and maintains the mesenchymal morphology of fibroblasts (35)(36)(37). STRAP is ubiquitously expressed, and STRAP Ϫ/Ϫ mice are embryonically lethal (38).…”
mentioning
confidence: 99%